Complex Regulatory Network Controls Initial Adhesion and Biofilm Formation in Escherichia coli via Regulation of the csgD Gene - Prigent-Combaret, Claire (American Society for Microbiology, 2001)
The Escherichia coli OmpR/EnvZ two-component regulatory system, which senses environmental osmolarity, also regulates biofilm formation. Up mutations in the ompR gene, such as the ompR234 mutation, stimulate laboratory strains of E. coli to grow as a biofilm community rather than in a planktonic state. In this report, we show that the OmpR234 protein promotes biofilm formation by binding the csgD promoter region and stimulating its transcription. The csgD gene encodes the transcription regulator CsgD, which in turn activates transcription of the csgBA operon encoding curli, extracellular structures involved in bacterial adhesion. Consistent with the role of the ompR gene as part of an osmolarity-sensing regulatory system, we also show that the formation of biofilm by E. coli is inhibited by increasing osmolarity in the growth medium. The ompR234 mutation counteracts adhesion inhibition by high medium osmolarity; we provide evidence that the ompR234 mutation promotes biofilm formation by strongly increasing the initial adhesion of bacteria to an abiotic surface. This increase in initial adhesion is stationary phase dependent, but it is negatively regulated by the stationary-phase-specific sigma factor RpoS. We propose that this negative regulation takes place via rpoS-dependent transcription of the transcription regulator cpxR; cpxR-mediated repression of csgB and csgD promoters is also triggered by osmolarity and by curli overproduction, in a feedback regulation loop.